Avaliação dos efeitos o óleo essencial de lippia sidoides cham. e do timol durante o cultivo in vitro de folículos pré-antrais inclusos em tecido ovariano bovino - Caetano Filho, Francisco Freire (2023)
The aim of this study was to evaluate the effects of adding Lippia sidoides essential oil (LSEO) and its active compound thymol during the in vitro culture of preantral follicles included in bovine ovarian tissue, in order to assess follicle activation, development, viability and morphological integrity. As well as the configuration of the extracellular matrix (ECM), expression of mRNA for SOD, CAT, PRDX6 and GPX1 and quantification of the antioxidant environment through thiol content and activity of the enzymes superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPX). To carry out this study, all the chemical products, including Lippia sidoides essential oil and Thymol, were purchased commercially by Laszlo and Sigma-Aldrich Brasil Ltda, respectively. Subsequently, in situ culture was carried out, where the ovarian cortex was divided into fragments of approximately 3x3x1 mm which were then cultured for 6 days in 24-well plates containing 0.5 mL of α-MEM+ medium alone or supplemented with different concentrations of Lippia sidoides essential oil (400, 800, 1,600, 3,200 μg/mL) or thymol (400, 800, 1,600, 3,200 μg/mL μg/mL). The culture medium was partially changed (60%) every 2 days. At the end of the cultivation period, part of the fragments were fixed and subjected to histological analysis, and part of the fragments were frozen at -80ºC for biochemical and molecular analysis. The results showed that the addition of 400µg and 800µg/mL of LSEO and thymol to the culture medium showed better rates of morphologically normal follicles when compared to the other treatments tested. The 400µg/mL concentration of LSEO and thymol promoted the best rates of follicle activation and development, as well as increasing collagen levels and stromal density in both experiments. The gene expression results showed that the concentration of 800µg//mL in the thymol treatment reduced the mRNA levels for SOD, CAT and PRDX6 and did not influence the expression of GPX1. In the analysis with LSEO, the concentration of 800µg/mL maintained the expression of SOD, CAT and PRDX6 while increasing the expression of GPX1 in relation to the cultured control. With regard to the thiol profile and the antioxidant activity of the CAT, SOD and GPX enzymes, in the treatment with thymol only the 800µg/mL concentration caused an increase in CAT levels and a reduction in SOD levels, but did not influence the thiol and GPX values, while in the treatment with LSEO only the 400µg/mL concentration of the oil increased GPX levels, but did not influence the activity of the other enzymes. In conclusion, the presence of Thymol and Lippia sidoides essential oil in the in vitro culture medium romotes the maintenance of follicular viability, induces greater activation and development of follicles, and attenuates and modulates oxidative stress.